Photography, railways and landscape in Transylvania, Romania : case studies in digital humanities (2019)
‘An idea, not a thing,’ landscape is the cultural perception of the physical environ- ment, ‘created by our minds and emotions’ (Clark et al. 2003: 3). The environment as physical place and the landscape as culturally determined perception and representation of the physical place, therefore, form a complex unity. Among the different representations of the environment (or landscape-construction means), cartography and statistics are allegedly more objective, while photography, painting, and literature provide rather subjective readings. Through mapping, contemporary geo-positioned data-management tools allow for a multi-layered relatedness between these two components of landscape.